Responding to the "unknown assailant": A qualitative exploration with Australian health and aged care chaplains on the impact of COVID-19. Issue 3 (3rd July 2022) - Jones, Kate Fiona; Washington, Jennifer; Kearney, Matthew; Best, Megan C.
Abstract: The global coronavirus pandemic (COVID-19) has brought about physical, psychological and spiritual challenges within health and aged care services across Australia. The aim of this study was to consider the impact of COVID-19 from the perspective of Australian chaplains. Semi-structured interviews were conducted with 17 chaplains. A grounded theory analysis identified three overarching themes: (1) a changing healthcare environment; (2) the impact of the virus; and (3) chaplains responding to the crisis. Increased healthcare restrictions in response to COVID-19 raised levels of fear and anxiety among patients, residents, family members and staff, and generated feelings of isolation and disconnection. Chaplains responded by providing a calm presence, being available, holding out hope, introducing creative ways to provide spiritual care and seeking spiritual nourishment themselves. The value of chaplaincy in health and aged care services is discussed in light of these findings.